Disability as a fluid state - Barnartt, Sharon N. (Bingley, U.K. : Emerald, 2010)
Disability is often described in a way that suggests that it is most often a permanent state. Many concepts and models of disability suggest this. Even when it is described as being socially constructed, the implication is that an impairment leads to a permanent status of disabled within that social, cultural or historical milieu. But there is a lot of evidence that disability is a fluid state. The relationship between impairment (physical state) and disability is neither fixed nor permanent but is fluid and not easily predicted. This volume revolutionarily reconceptualizes disability not as a static but a dynamic phenomenon which is related to social, cultural, psychological and historical context. Papers by leading disability scholars in the areas of sociology, anthropology and history examine this premise from many points of view. Several look at micro-level interactional processes over time, some look at cultural change over time and their effects on definitions and measurements, and some look at how social processes shape physical conditions into disabilities or impairments/disabilities into normality. All examine the fluidity of disability and rethink how we measure it.
Disability as a fluid state : introduction / Sharon N. Barnartt -- 'Feeling normal' and 'feeling disabled' / Mary Jo Deegan -- Out of a coma and into a wheelchair : social and physical accessibility and the construction of disabled identity / Jay Chaskes -- At the interstices of classification : notes on the category of disability in sub-Saharan Africa / Patrick J. Devlieger -- A relational approach to the development of civil rights for people with intellectual disabilities / Allison C. Carey -- From 'survival of the fittest' to 'fitness for all' to 'who defines fitness anyway?' : 100 years of (U.S.) sociological theory on disability / Corinne Kirchner -- Regarding disability : perceptions of protection under the Americans with disabilities act / Pepper K. Mueller, Jeffrey A. Houser, Mark D. Riddle -- 'Sit home and collect the check' : race, class, and the social construction of disability identity / Deborah L. Little -- Activism, models, identities, and opportunities : a preliminary test of a typology of disability orientations / Rosalyn Benjamin Darling, D. Alex Heckert -- Deaf women's work experiences : negotiating gender, ability, and theories of resistance / Cheryl Najarian Souza -- Why does growth hurt? The dual role of normalization and stigmatization in the experience of growth hormone treatment / Leslie Rott -- Disproportionality : a sociological perspective on the identification by schools of students with learning disabilities / Dara Shifrer, Chandra Muller, Rebecca Callahan.
Print version record
Keywords: Sociology of disability; People with disabilities